Risks and risk management in modern multiple sclerosis immunotherapeutic treatment. (March 2019) - Klotz, Luisa; Havla, Joachim; Schwab, Nicholas; Hohlfeld, Reinhard; Barnett, Michael; Reddel, Stephen; Wiendl, Heinz
In recent years, there has been a paradigm shift in the treatment of multiple sclerosis (MS) owing to the approval of a number of new drugs with very distinct mechanisms of action. All approved disease-modifying drugs primarily work directly on the immune system. However, the identification of an 'optimal choice' for individual patients with regard to treatment efficacy, treatment adherence and side-effect profile has become increasingly complex including conceptual as well as practical considerations. Similarly, there are peculiarities and specific requirements with regard to treatment monitoring, especially in relation to immunosuppression, the development of secondary immune-related complications, as well as the existence of drug-specific on- and off-target effects. Both classical immunosuppression and selective immune interventions generate a spectrum of potential therapy-related complications. This article provides a comprehensive overview of available immunotherapeutics for MS and their risks, detailing individual mechanisms of action and side-effect profiles. Furthermore, practical recommendations for patients treated with modern MS immunotherapeutics are provided.